The bridge between social identity and community capital on the path to recovery and desistance - Best, David (Probation journal, 2018)
It has long been recognised that changes in social networks (and the underpinning changes in personal and social identity) are strong predictors of both desistance from crime and recovery from substance use. Building on existing work attempting to measure and shift social networks and transitions to prosocial groups, the current study provides pilot data from prisoners and family members about a visualisation technique widely used in specialist addiction treatment (node-link mapping) to map opportunities for linkage to prosocial groups and networks. The data presented in the paper are from a small-scale feasibility pilot. This suggests both bonding and bridging capital in prisoner populations due for release and the diversity of community capital opportunities that exists in this population. The implications of this work are significant for substance users and offenders pending return to the community, and has implications around resettlement and reintegration support for probation staff in prisons and in the community. The paper emphasises the importance of mapping connectedness as a key component of planning for reintegration back into the community for those working with offenders who are aspiring to achieve desistance and recovery.